Sosialisai Bahaya Dan Pencegahan Hipertensi Di Dusun Waimolong Provinsi Maluku - Ety Dusra; Epi Dusra (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesia is starting to enter a period of population aging where there is an increase in life expectancy followed by an increase in the number of elderly people which is predicted to continue to increase until 2035 to 48.2% of people (15.77%). Maluku recorded the highest number of hypertension cases in Maluku Province with a total of 25,410 cases in 2020. The aim of implementing community service activities in Hitu Village is to increase community awareness, especially the elderly, regarding the dangers and prevention of hypertension. The activities carried out were elderly gymnastics and continued with socialization in Waimolong Hamlet using the question and answer discussion method. The results of the community service implementation went smoothly and enthusiastically from the participants, as seen from the participant attendance list of more than 25 people, based on the results of questions and answers and interviews, the participants were able to understand that hypertension can be prevented and controlled by living a healthy lifestyle, eating healthy foods. being nutritious, doing physical activity, not smoking or reducing the number of cigarettes consumed per day and carrying out regular health checks at the local health center. There needs to be regular exercise activities carried out in Waimolong Hamlet.